Respons Pertumbuhan dan Produksi Beberapa Varietas Sorgum (Sorghum bicolor (L.) Moench)Pada Berbagai Jarak Tanam di Lahan Kelapa Sawit TBM I - Zulkarnaen Zulkarnaen; T Irmansyah; Irsal. Irsal. (Jurnal Agroekoteknologi, 2015)
This research was conducted to study the varieties and various spacing  on the growth and yield ofthe sorghum under the immature plants 1 of oil palm land. The research was held at Paya Robahvillage, west Binjai district, north Sumatra province from June-September 2014, using split plotdesign with varieties (numbu and kawali) as main plot and spacing (75x15, 75x20, 75x25, 75x30cm) as sub plot. Parameter observed were plant height, stem diameter, flowering time, harvestingtime, weight of panicle seed per sample, weight of panicle seed per sub plot, yield per sample, yieldper sub plot, and 1000 grains weight. The result showed that varieties significantly effect on plantheight, stem diameter, weight of panicle seed per sample, weight of panicle seed per sub plot, yield per sub plot, and 1000 grains weight. Spacing was significantly effect on plant height, stemdiameter, flowering time, harvesting time, weight of panicle seed per sub plot, yield per sub plot.There  were interaction between variety and spacing for stem diameter.  Keywords: spacing, variety, sorghum